Comparative study of polysaccharide metabolites in purple, orange, and white Ipomoea batatas tubers - Xiuzhi Wang; Xiaolin Wan; Jiaqi Wu; Lingjun Cui; Qiang Xiao (Food Chemistry: X)
We employed LC-MS/MS to investigate the metabolic profiles of polysaccharide compounds in white, orange, and purple sweet potato flesh. Comparisons between Orange vs White, Purple vs Orange, and Purple vs White identified 69 polysaccharide metabolites, including 23, 36, and 44 differential metabolites, respectively, with distinct differentiation. Among the three sample groups, 14 polysaccharide compounds and 2 anthocyanins exhibited significant differences. Our further analysis indicated that anthocyanins occupy a central position in the related network diagram and are interconnected with polysaccharides. In metabolic pathways, sucrose and the anthocyanin precursor UDP-glucose were upregulated in purple sweet potatoes, along with elevated levels of pelargonidin 3-O-β-D-sambubioside and delphinidin 3,5-diglucoside. Conversely, sucrose was downregulated in purple sweet potatoes while increasing in white and orange varieties. Therefore, we hypothesize that the competition between sugars and anthocyanins for shared biosynthesis precursors is attributed to differential polysaccharide metabolites among sweet potato tubers of three colors.